Learning success in out-of-school sports activities (based on OKM data for 2016) (Training and Practice : Journal of Educational Sciences, 2019)
The purpose of our study is to highlight the connection between the participation of students in out-of-school sports activities and their success in school on the basis of the analysis of the 10th-year student questionnaires of the 2016 OKM database. As for out-of-school extra and private lessons, sports activities seem to be the most popular with students. Concerning gender and school grade average, boys and students with a better school grade average take part in sports activities unlike girls and students with a lower school grade average.